Spasm and electromyography intensity of bilateral extensor during relaxation period in trunk anterior flexion–extension performance response to sustained asymmetry spinal loading - Longzhen Wang; Jingyuan Wang; Wenjin Wang; Xiangrong Cheng; Wenrong Wang; Xinhai Shan (BMC Musculoskeletal Disorders)
Abstract Background The influence of sustained spinal loading on flexion relaxation phenomenon (FRP) in erector spinae (ES) in trunk anterior flexion–extension performance has been studied. However, no investigation has been reported on spasm after the loading. The aim of the study is to test if spasm as well as the increase of electromyography ( EMG) intensity of extensors in relaxation period could be found during and/or after prolonged asymmetric static loading. Methods Twenty six male healthy college students participated in the study. Participants finished two 30 min asymmetry load conditions (left load(LL), right load (RL)), randomly with total load 10 kg on the left or the right shoulder, respectively. EMG signals were recorded from the left(l) and the right(r) thoracic erector spinae (lTES, rTES), lumbar erector spinae (lLES, rTES), and hamstring (lHAM, rHAM) muscles in the first 10 min and the last 10 min during the interventions, and also recorded in three trunk anterior flexion–extension exertions before (pre) and after (post) the interventions, respectively. The rhythmic of flexion–extension performance was controlled by a metronome with 5 s flexion and 5 s extension at 60 Hz. Spasms were evaluated and an averaged electromyography (NEMG) was calculated for extensors at the first and last 10 min of 30 min intervention, as well as in the relaxation period of FRP during flexion–extension exertion in both pre and post the intervention. Results During asymmetry spinal loading process, there was no sign of spasms in any of extensors. NEMG of multiple erect spinae had a significant decrease (with the largest -60%, p = 0.021 in rLES in LL) while that of hamstring increases significantly (the largest value 139%, p = 0.001 in lHAM in LL). After the interventions, the prevalence of spasms in extensors in relaxation period was found with the value from 8 to 55%. Also, NEMG in multiple extensors had a significant increase (with the largest increase of 114% in lLES in LL, p = 0.023). Conclusion During sustained asymmetry spinal loading, the NEMG in bilateral HAM has significant increase and the NEMG in bilateral erect spinea has a decrease tendency. After loading, the NEMG has a significant increase, in parallel with spasms elicited in multiple extensors in relation period in flexion–extension performance, with no significant difference between bilateral sides. It may indicate that sustained asymmetry spinal loading could lead to a weakness for tension ability, and/or a micro-damage in spinal bilateral passive tissues in low back area, the risk of developing low back disorder.